Optimization of Purposes of Islamic Sharia and Their Rules in Creating Law for Contemporary and Actual Issues | تفعيل مقاصد الشريعة وضوابطه في تنزيل الأحكام على النوازل والمستجدات - Refki Saputra (Al-Zahra : Journal for Islamic and Arabic Studies, 2018)
It has been stated in the Islamic Sharia that the purposes of the Sharia have an important role and a great authority in the implementing a law on the calamities and facts and developments. Those refer to Sharia’s spirit, principle and structure. After being excerpted from an Islamic text, decisive law of phenomena should aim to realize benefits and pearls of wisdom in a society. This article reveals the reasons for the importance of Purposes of the Sharia and their tools in creating a law. In this article, also, are included several models in their application existing in the Prophet’s hadith